The identity of Senegalia saltilloensis (Fabaceae) = La identidad de Senegalia saltilloensis (Fabaceae) - Villarreal Quintanilla, José Ángel; Encina Domínguez, Juan Antonio; Estrada Castillón, Andrés Eduardo (2018)
AbstrAct: Background and Aims: The mimosoid genera Senegalia and Acacia are closely related. Acacia sensu lato is a polyphyletic group that can be split in the following genera: Vachellia, Senegalia, Acaciella and Mariosousa, remaining as Acacia (sensu stricto) only the “Australian species” and some others from the Pacific Islands. The American species of Senegalia and the new genus Mariosousa include the elements of Acacia subgenus Aculeiferum. We agree with this criterion. Senegalia saltilloensis was described by Britton & Rose in 1928, followed by synonymization with S. roemeriana, and was later re-evaluated as a valid species, creating a new nomenclatural combination in the genus Acacia. The aim of this study was to know the identity of the poorly known plants named as Senegalia saltilloensis. Methods: A morphometric analysis was carried out. A total of 70 specimens were examined and 21 characters were evaluated to find the similarity between Senegalia saltilloensis and Senegalia roemeriana. Key results: The results show no significant morphological difference between the two entities. Conclusions: The name Senegalia saltilloensis should be maintained as synonym of the well- known name of Senegalia roemeriana. Key words: Acacia roemeriana, Mimosoideae, morphometric analysis, multivariate analysis.